Noms généraux et anaphore : une histoire de parties et de membres - Mathilde Salles (Studii de Lingvistica)
The affinities between general nouns and two types of anaphora, resumptive anaphora and co-referential anaphora with lexical shift, are frequently emphasized in studies devoted to this category of nouns. Their weak classifying power explains both their predisposition to enter into these two types of anaphora and some limits of their use in co-referential anaphora. In this paper, we also study their relationship with another type of anaphora, associative anaphora. The referential versatility of a general noun as partie ‘part’, for example, which would predispose it to reiterations of any type of previously named part, would it not be just as effective to refer to parts or some parts of a whole after having mentioned this one?